Penggunaan Sonkeigo oleh Mahasiswa Magang Indonesia di Lingkungan Kerja Gas Station di Hiroshima, Jepang: Kajian Sosiolinguistik - Firdause, Annisa Tiara; Karnawati, Rita Agustina (Vocational College of Diponegoro University, 2025)
This study analyzes the use of sonkeigo in the scope of work at a gas station company in Hiroshima, Japan and the difficulties faced by Japanese language learners regarding the use of sonkeigo. The method used is descriptive qualitative with interviews, observations and documentation. The theory used is Fishman's theory (1972). This study aims to determine sonkeigo speech acts in real-world interactions between students who have interned in Japan and native speakers, and to analyze the realistic and social difficulties faced by these students in applying sonkeigo in a professional in a gas station company. Based on the results. The use of sonkeigo in service can be identified through several linguistic characteristics, namely the addition of the verbs